Five key takeaways on the irrational use of antimicrobials in livestock and aquaculture systems in low- and middle-income countries - Moodley, Arshnee; Muloi, Dishon M.; Hoffmann, Vivian; Murphy, Mike; Rheman, Shafiq; Hossain, Sabrina; Verner-Jeffreys, David; Khor, Laura; Delamare-Deboutteville, Jerome; Patel, Ekta (International Livestock Research Institute, 2024)
This brief is important for policymakers, researchers, animal health service providers, and agricultural stakeholders in low- and middle-income countries. Crucial insights are provided into drivers of antimicrobial misuse in livestock and aquaculture, providing evidence-based recommendations for improving antimicrobial use practices. By understanding the gaps in diagnostic services, regulatory frameworks, and farmers’ education, stakeholders can design targeted interventions to promote responsible antimicrobial use. Strengthening regulatory frameworks in these areas will help mitigate antimicrobial resistance, protect animal and human health, and ensure that the animal and aquatic food sector can move toward more sustainable, antibiotic-free production systems in low- and middle-income countries.